Swift heavy ion irradiation induced microstructural modification and evolution of photoluminescence from Si rich a-SiNx:H. (16th April 2015) - Bommali, R K; Ghosh, S; Prakash, G Vijaya; Kanjilal, D; Mondal, P; Srivastava, A K; Srivastava, P
Abstract: Silicon-rich silicon nitride (SRSN) films having two different compositions were irradiated with 100 MeV of Ni 7+ ions at fluences of 5 × 10 12 ions/cm 2 and 1 × 10 14 ions/cm 2 . The films, despite having different compositions, showed similar microstructural evolution, as evidenced in cross-sectional transmission electron microscopy (XTEM). Discontinuous tracks (∼2 nm wide) appeared under a fluence of 5 × 10 12 ions/cm 2, and they overlapped and dissolved at an increased fluence of 1 × 10 14 ions/cm 2 . The corresponding changes in photoluminescence (PL) of the films were investigated with three lasers with the aim of tracking the evolution of different radiative processes in SRSN with ion fluence. The evolution of PL with fluence was well correlated with microstructural evolution. PL results showed that ion irradiation progressively leads to the simultaneous creation of both radiative and non-radiative defects, with the latter dominating at higher fluences. The results are understood on the basis of a thermal spike model of ion–materials interaction.